Hibiscus tiliaceus ethanolic leaf extract modulates quorum sensing-facilitated virulence factors - MILDA HUSNAH; SUHARTONO SUHARTONO; YULIA SARI ISMAIL (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Husnah M, Suhartono S, Ismail YS. 2023. Hibiscus tiliaceus ethanolic leaf extract modulates quorum sensing-facilitated virulence factors. Biodiversitas 24: 5962-5971. Bacterial pathogenicity and infections are often associated with the presence of virulence factors generated mostly through quorum-sensing (QS) mechanisms. Therefore, QS suppression is considered an effective strategy for combatting pathogens. Many studies to search for new anti-QS agents, particularly those of plant origin, have been intensively conducted. Hibiscus tiliaceus L. is one of the medicinal plants exhibiting various pharmacological activities including antibacterial potential; however, the study regarding its effects on bacterial QS systems has not been reported. Therefore, this study aimed to investigate the potency of Hibiscus tiliaceus ethanolic leaf extract (HELE) as a modulating agent against Chromobacterium violaceum ATCC122472, Staphylococcus aureus ATCC 29213, and Pseudomonas aeruginosa PA01. The extract was obtained through maceration and phytochemical screening was carried out by GC-MS. To evaluate antibacterial and anti-QS potentials of HELE, minimum inhibitory concentration (MIC); minimum bactericidal concentration (MBC); growth inhibition rate; disc diffusion; and inhibition of violacein, pyocyanin, swarming motility, and biofilm formation were assayed. Statistical analysis was performed using SPPS software and Analysis of Varian (ANOVA) was employed to determine significant differences between the control and treatment groups. Phytochemical screening revealed the presence of 16 different compounds in HELE, represented predominantly by diterpenoids (phytol), fatty acids (palmitic acid and oleic acid), and p-Tolualdehyde. MIC was found at 10 mg/mL against both C. violaceum ATCC122472 and S. aureus ATCC 29213, and 160 mg/mL against P. aeruginosa PA01. The MBC for the first two bacteria was 20 mg/mL, whereas that against P. aeruginosa PA01 remains to be determined. HELE was able to suppress the production of violacein, pyocyanin, and swarming motility at sub-MIC concentrations, highlighting the anti-QS potential of the extract. HELE at sub-MICs was found to stimulate biofilm formation, whereas at 2 x MIC exhibited an inhibitory effect. These findings justified that HELE might serve as a promising candidate not only as a future QS-inhibitory but also as a concentration-dependent QS-modulating agent.